Cooperative spectrum sharing with multi-antenna based adaptive hybrid relay in presence of multiple primary users. Issue 6 (18th August 2017) - Saha, Animesh; Bhattacherjee, Subhra Shankha; De, Chanchal Kumar; De, Debasis
Abstract: Performance analysis of cooperative spectrum sharing network using multi-antenna based Adaptive Hybrid Relay (AHR) scheme in presence of multiple primary users under non-identical Rayleigh fading channel has been studied in this paper. An Adaptive Hybrid Relay equipped with multiple antennas at the input employs selection combining (SC) on the signals received from secondary user source (S) via multiple receiving antennas at the input and forwards the received signal to secondary user destination (D). The outage probability has been evaluated at the secondary destination where best relay selection (BRS) scheme is used. The comparison between outage performances of cooperative spectrum sharing for Amplify-and-Forward (AF), Decode-and-Forward (DF) and Adaptive Hybrid Relay (AHR) scheme is also presented. The effects of number of relay antennas (L), number of relays (K) and number of primary users (M) on the system performance have also been studied. It is seen that the outage performance improves considerably with increase in number of primary users (PUs). It is also observed that increase in number of primary users compensate the negative impact of high channel rate (R). A trade-off between number of relay and number of antenna at each relay is also shown.